Autoantibodies in Post-Epstein-Barr Acute Cerebellar Ataxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Eight of 23 patients with acute cerebellar ataxia (ACA) following Epstein-Barr virus (EBV) infection (proven serologically) had increased IgM anti-triosephosphate isomerase (TPI) antibody titers, in a study at Kyorin University, Tokyo, and Kinki University, Osaka, Japan.